ANTARA HAMBA JAJAHAN ATAU WARGA NEGARA: PRIBUMI DALAM RUANG KEWARGANEGARAAN LOKAL 1848-1940 - Ahmad Fahmil Aziz (Lambung Mangkurat University, 2025)
Untill 1940, the citizenship system in the Dutch East Indies had undergone several changes. This culminated in the official enactment of the Algemene Bepalingen van wetgeving voor Indonesie, which was reinforced by Article 109 of the Regeringsreglement and then Article 163 of the Indische Staatsregeling. These regulations divided the population of the Dutch East Indies into three groups: 1) Europeans, 2) Vreemde Oosterlingen, and 3) Inlanders. This policy creates social segregation in the citizen hierarchy. The citizenship system became exclusive, placing Europeans as first-class citizens, while Indigenous people were placed as lower-class citizens. This article explains the status of Indigenous people in the colonial citizenship system and practices from 1848 to 1940. The purpose of this research is to analyze the citizenship status of Indigenous people through civil registration as the primary instrument of legitimacy as citizens. This research uses historical research methods that include topic selection, heuristics, source criticism, interpretation, and historiography. The findings show, first, that the colonial citizenship system created superiority and inequality among citizens, both in legal and formal aspects and in socio-political practices. Second, colonial citizenship practices recognized Indigenous people as slaves of the colonized rather than as first-class citizens.